Keterbatasan radiografi panoramik dalam pengukuran ketidaksimetrisan mandibula - Barunawaty Yunus (Journal of Dentomaxillofacial Science, 2007)
Panoramic radiography is a technique to yield face structure photo including bone ofmaxilla, mandible and supporting structures like maxilla antrum, nasal fossa, TMJ,procesus styloideus, and os. hyoid. Panoramic radiography is also used to evaluateasymmetrical of face. Growth and development of head is similar to the growth anddevelopment of body in general. The skeletal morphology can be disturbed by internaldisorder of TMJ and degenerative joint disease as short ramus, a sharp angle of mandible,and also cranial base that cause asymmetrical face. By taking accurate panoramicradiography, the mandible asymmetrical can be measured.